States versus markets : the emergence of a global economy - Schwartz, Herman M., 1958- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmi llan, 2010)
"States versus Markets shows that globalization is not a novel pheno menon but a recurrent process whereby markets have, since the sixteenth century, periodically redistributed economic activity. This revised an d updated new edition takes account of the new rise of Asia and the glo bal financial crisis originating in the US housing finance system"--Pro vided by publisher.
States, agriculture, and globalization -- The rise of the modern sta te : from street gangs to mafias -- States, markets, and the origins of international inequality -- Economic and hegemonic cycles -- The Indus trial Revolution and late development -- Agricultural exporters and the search for labor -- Agriculture-led growth and crisis in the periphery : Ricardian success, Ricardian failure -- The collapse of the nineteen th-century economy : the erosion of hegemony? -- The fall and rise and fall again of globalization -- The Depression, US domestic politics, an d the foundation of the post-World War II system -- International money , capital flows, and domestic politics -- Transnational firms : a war o f all against all -- Industrialization in the old agricultural peripher y : the rise of the newly industrialized countries -- Trade, protection , and renewed globalization -- US hegemony : declining from below? -- U S hegemony and global stability : reviving or declining from the top do wn?
Includes bibliographical references and index.
Keywords: International economic relations; Industrial Policy; Commercial policy